2004
DOI: 10.1523/jneurosci.0122-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Resistance of Oligodendrocytes to Prion Infection

Abstract: Within the CNS, the normal form of cellular prion protein (PrP C ) is expressed on neurons, oligodendrocytes, and astrocytes. The contribution of these cell types to prion replication and pathogenesis is unclear. To assess the role of oligodendrocytes, we expressed PrP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 39 publications
(42 reference statements)
2
37
0
1
Order By: Relevance
“…29 In the human brain, pathologic studies of terminal CJD reported axonal damage, and suggested the possibility of retrograde axonal transport of prions, infecting multiple sites along neuroanatomic pathways. 27,[30][31][32] In the Japanese panencephalopathic variant (pCJD), WM damage has been noted in the internal capsule, brain stem, and middle cerebellar peduncles, 33 consistent with our imaging findings. In vCJD (the variant CJD associated with consumption of tainted beef), vacuolation, PrP deposition, and glial cell reaction were observed in the cortical WM of all 11 cases studied.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…29 In the human brain, pathologic studies of terminal CJD reported axonal damage, and suggested the possibility of retrograde axonal transport of prions, infecting multiple sites along neuroanatomic pathways. 27,[30][31][32] In the Japanese panencephalopathic variant (pCJD), WM damage has been noted in the internal capsule, brain stem, and middle cerebellar peduncles, 33 consistent with our imaging findings. In vCJD (the variant CJD associated with consumption of tainted beef), vacuolation, PrP deposition, and glial cell reaction were observed in the cortical WM of all 11 cases studied.…”
Section: Discussionsupporting
confidence: 89%
“…While predominantly neuronal, PrP C (the nor- mal cellular precursor protein) is also expressed in astrocytes and oligodendrocytes. 27 PrP C appears to be necessary for myelin protection and maintenance 28 ; its replacement by PrP Sc in CJD may well cause myelinopathy. This finding has now been extended to the early development of Prnp 0/0 mice, which display deficits in motor coordination and balance and vacuolation in several WM tracts at age 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…12 Transgenic mice expressing PrP under the control of the myelin basic protein-promoter are resistant to prion infection, suggesting that oligodendrocytes and Schwann cells do not support cell-autonomous prion replication and neural spread of prions. 31 We found that tg550 PLP mice (n ϭ 8), which expressed low amounts of PrP-Fc 2 , showed delayed disease over tamoxifen-treated tg550Stop and PLP/Cre-ERT2 mice. The delay was 35 days (P Ͻ 0.01) after intracerebral inoculation (Figure 5e) and 50 days (P Ͻ 0.01) after intraperitoneal inoculation (Figure 5f).…”
mentioning
confidence: 73%
“…org). Expression of PrP-Fc 2 was relatively weak in tg550 PLP oligodendrocytes (maybe because the Prnp promoter is weakly active in oligodendrocytes 30,31 ), but undetectable in neurons and astrocytes (see Supplemental Figure S2 at GFAP mice showed delayed disease after intracerebral inoculation (151 and 65 days, respectively; P Ͻ 0.01) ( Figure 5, a and c) and after intraperitoneal inoculation (90 and 65 days, respectively; P Ͻ 0.01) ( Figure 5, b and d). Astrocytes have been shown to be competent for prion replication, 32 although the toxicity of astrocytic PrP Sc to neurons is somewhat controversial.…”
mentioning
confidence: 99%
“…We therefore crossed ⌬PrP o mice to tg640 mice, which express full-length PrP C under transcriptional control of a myelin basic protein promoter fragment (Fig. 4a) (Prinz et al, 2004).…”
Section: Oligodendroglial Prpmentioning
confidence: 99%